Predicting functional communication ability in children with cerebral palsy at school entry. (12th November 2014) - Coleman, Andrea; Weir, Kelly; Ware, Robert S; Boyd, Roslyn
<x xml:space="preserve">Abstract</x> Aim To explore the value of demographic, environmental, and early clinical characteristics in predicting functional communication in children with cerebral palsy (CP) at school entry. Method Data are from an Australian prospective longitudinal study of children with CP. Children assessed at 18 to 24 and 48 to 60 months corrected age were included in the study. Functional communication was classified at 48 to 60 months using the Communication Function Classification System (CFCS). Predictive variables included communication skills at 18 to 24 months, evaluated using the Communication and Symbolic Behavioural Scales Developmental Profile (CSBS‐DP) Infant‐Toddler Checklist. Early Gross Motor Function Classification System (GMFCS), Manual Ability Classification System, and motor type and distribution were evaluated by two physiotherapists. Demographic and comorbid variables were obtained through parent interview with a paediatrician or rehabilitation specialist. Results A total of 114 children (76 males, 38 females) were included in the study. At 18 to 24 months the mean CSBS‐DP was 84.9 (SD 19.0). The CFCS distribution at 48 to 60 months was I=36(32%), II=25(22%), III=20(18%), IV=19(17%), and V=14(12%). In multivariable regression analysis, only CSBS‐DP (p<0.01) and GMFCS (p<0.01) at 18 to 24 months were predictors of functional communication at school entry. Interpretation Body structure and function and not environmental factors impact functional communication at school entry in children with CP. This provides valuable guidance for early screening, parent education, and future planning of intervention programs to improve functional communication.